Analisis Kritik Sosial Dalam Kumpulan Puisi Negeri Fufu Fafa Karya Sosiawan Leak: Tinjauan Sosiologi Sastra - Nevi Samudra Permatasari; Indayani (Stilistika: Jurnal Pendidikan Bahasa dan Sastra, 2026)
This study aims to describe social criticism in the poetry collection Negeri Fufu Fafa by Sosiawan Leak. The poetry collection contains various social phenomena in society. Through his works, Sosiawan Leak consistently voices critical responses to various social deviations. This study uses a descriptive qualitative approach with a library research method. The data source is the poetry collection Negeri Fufu Fafa, while the data consist of words, phrases, sentences, lines, and stanzas containing social criticism. The results show that the poetry collection contains social criticism in the fields of religion, economy, politics, morality, education, and technology. Religious criticism highlights fanaticism and deviations from religious values, economic criticism describes social inequality, while political criticism reveals abuse of power and nepotism. Moral criticism indicates declining social integrity, educational criticism highlights damaged academic integrity, and technological criticism describes the misuse of social media for popularity and commercialization. This study shows that poetry plays an important role as a medium of reflection and social control in society.